A Multidisciplinary Evaluation of Prescribing Practices for Prophylactic Antibiotics in Operative and Nonoperative Facial Fractures. Issue 8 (November 2015) - Brooke, Sebastian M.; Goyal, Neerav; Michelotti, Brett F.; Guedez, Henry Montilla; Fedok, Fred G.; Mackay, Donald R.; Samson, Thomas D.
Abstract : Background: Evidence supports short-term perioperative prophylaxis for facial fractures. It is unknown, however, whether there is any professional consensus on how to manage these injuries. No multidisciplinary evaluation of the prophylactic antibiotic prescribing patterns for neither operative nor nonoperative facial fractures has been performed. Aim: To evaluate the prophylactic antibiotic prescribing patterns of multiple specialties in operative and nonoperative facial fractures. Methods: A 14 question anonymous online-based survey was distributed to members of the American Society of Maxillofacial Surgeons (ASMS) and the American Association of Facial Plastic Surgeons to evaluate current practices. Results and Conclusions: 205 respondents, including 89 plastic surgeons, 98 otolaryngologists, 12 oral and maxillofacial surgeons, and 7 with double board certification practicing throughout the United States with ranging experience from 11 to 30 years. As expected, preoperative, perioperative, or postoperative prophylactic antibiotics are either "always" or "sometimes" prescribed, 100% of the time with more varied practice upon further inspection. A total of 85.1% either "always" or "sometimes" use antibiotics while awaiting surgery. Dentate segment fractures are the most frequent type of facial fractures to receive prophylactic antibiotics for both operative (90.5%) and nonoperative (84.1%) fractures. Duration of antibiotic use is more varied with the majority providing 3 to 7 days despite current evidence. First generation cephalosporins alone are prescribed by 49% of respondents, which may not adequately cover oral flora. There is no multidisciplinary consensus for prophylactic antibiotics for specific operative fracture types or nonoperative facial fractures, an area with little published evidence.